Effectiveness of the Implementation of Islamic Work Ethics (Core Values AKHLAK) at Bank Syariah Indonesia (BSI) in Bandung in Improving Employee Performance - Lestari, Rini; ., Nurfahmiyati; Lestira Oktaroza, Magnaz; Asfari Nur Hasanah, Laila; Sumarni Pratiwi, Liliani; Kamila, Zahra (KnE Social Sciences, 2023)
This research is a continuation of previous research. Previous research discusses the application of Islamic Work Ethics in Islamic Banking Institutions in the city of Bandung with a case study at Bank Syariah Indonesia. The reason for conducting these studies is because there is a violation of Sharia principles in Islamic banking institutions. This violation is in the form of fictitious financing which causes the level of non-performing financing to increase, thus causing the company’s performance to deteriorate. In connection with this condition, research was conducted on Islamic Work Ethics, because the violation of Sharia principles is related to the behavior of employees in Islamic banking institutions. This research has a long-term goal, namely, to be able to contribute to scientific development through the effective application of AKHLAK Core values in order to form a role model of Islamic Work Ethics in Islamic banking institutions. This study uses a research method with a qualitative descriptive approach with data collection techniques through questionnaires and depth-interviews. The results showed that AKHLAK is the core value of BUMN which is applied in Bank Syariah Indonesia, namely as a guideline for Islamic work ethics in the BUMN environment. AKHLAK consists of Trustworthiness, competent, harmonious, loyal, adaptive, and collaborative, has met the criteria of effectiveness, and can improve employee performance through aimed targets. Keywords: core value AKHLAK, employee performance, Bank Syariah Indonesia